How plants grow up. Issue 3 (18th March 2019) - McKim, Sarah M
Abstract: A plant's lateral structures, such as leaves, branches and flowers, literally hinge on the shoot axis, making its integrity and growth fundamental to plant form. In all plants, subapical proliferation within the shoot tip displaces cells downward to extrude the cylindrical stem. Following the transition to flowering, many plants show extensive axial elongation associated with increased subapical proliferation and expansion. However, the cereal grasses also elongate their stems, called culms, due to activity within detached intercalary meristems which displaces cells upward, elevating the grain‐bearing inflorescence. Variation in culm length within species is especially relevant to cereal crops, as demonstrated by the high‐yielding semi‐dwarfed cereals of the Green Revolution. Although previously understudied, recent renewed interest the regulation of subapical and intercalary growth suggests that control of cell division planes, boundary formation and temporal dynamics of differentiation, are likely critical mechanisms coordinating axial growth and development in plants.